Antithrombotic Therapy in Patients With Atrial Fibrillation and Acute Coronary Syndrome Treated Medically or With Percutaneous Coronary Intervention or Undergoing Elective Percutaneous Coronary Intervention: Insights From the AUGUSTUS Trial - Windecker, Stephan; Lopes, Renato D; Massaro, Tyler; Jones-Burton, Charlotte; Granger, Christopher B; Aronson, Ronald; Heizer, Gretchen; Goodman, Shaun G; Darius, Harald; Jones, W Schuyler; Aschermann, Michael; Brieger, David; et al. (Circulation (New York, N.Y.), 2019)
BACKGROUND: The safety and efficacy of antithrombotic regimens may differ between patients with atrial fibrillation who have acute coronary syndromes (ACS), treated medically or with percutaneous coronary intervention (PCI), and those undergoing elective PCI. METHODS: Using a 2×2 factorial design, we compared apixaban with vitamin K antagonists and aspirin with placebo in patients with atrial fibrillation who had ACS or were undergoing PCI and were receiving a P2Y12 inhibitor. We explored bleeding, death and hospitalization, as well as death and ischemic events, by antithrombotic strategy in 3 prespecified subgroups: patients with ACS treated medically, patients with ACS treated with PCI, and those undergoing elective PCI. RESULTS: Of 4614 patients enrolled, 1097 (23.9%) had ACS treated medically, 1714 (37.3%) had ACS treated with PCI, and 1784 (38.8%) had elective PCI. Apixaban compared with vitamin K antagonist reduced International Society on Thrombosis and Haemostasis major or clinically relevant nonmajor bleeding in patients with ACS treated medically (hazard ratio [HR], 0.44 [95% CI, 0.28-0.68]), patients with ACS treated with PCI (HR, 0.68 [95% CI, 0.52-0.89]), and patients undergoing elective PCI (HR, 0.82 [95% CI, 0.64-1.04]; Pinteraction=0.052) and reduced death or hospitalization in the ACS treated medically (HR, 0.71 [95% CI, 0.54-0.92]), ACS treated with PCI (HR, 0.88 [95% CI, 0.74-1.06]), and elective PCI (HR, 0.87 [95% CI, 0.72-1.04]; Pinteraction=0.345) groups. Compared with vitamin K antagonists, apixaban resulted in a similar effect on death and ischemic events in the ACS treated medically, ACS treated with PCI, and elective PCI groups (Pinteraction=0.356). Aspirin had a higher rate of bleeding than did placebo in patients with ACS treated medically (HR, 1.49 [95% CI, 0.98-2.26]), those with ACS treated with PCI (HR, 2.02 [95% CI, 1.53-2.67]), and those undergoing elective PCI (HR, 1.91 [95% CI, 1.48-2.47]; Pinteraction=0.479). For the same comparison, there was no difference in outcomes among the 3 groups for the composite of death or hospitalization (Pinteraction=0.787) and death and ischemic events (Pinteraction=0.710). CONCLUSIONS: An antithrombotic regimen consisting of apixaban and a P2Y12 inhibitor without aspirin provides superior safety and similar efficacy in patients with atrial fibrillation who have ACS, whether managed medically or with PCI, and those undergoing elective PCI compared with regimens that include vitamin K antagonists, aspirin, or both. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT02415400.
Keywords: antikoagulancia; Acute Coronary Syndrome; Female; pyridony; kombinovaná terapie; Atrial Fibrillation; výsledek terapie; ženské pohlaví; Aspirin; Anticoagulants; antagonisté purinergních receptorů P2Y; kardiovaskulární látky; Pyrazoles; krvácení; Vitamin K; lidé; pyrazoly; Elective Surgical Procedures; koronární angioplastika; Platelet Aggregation Inhibitors; Pyridones; Treatment Outcome; hospitalizace; Percutaneous Coronary Intervention; prospektivní studie; proporcionální rizikové modely; vitamin K; fibrinolytika; Combined Modality Therapy; Aged; Cardiovascular Agents; Male; Proportional Hazards Models; Hospitalization; Prospective Studies; Purinergic P2Y Receptor Antagonists; Hemorrhage; kombinovaná farmakoterapie; Disease Management; inhibitory agregace trombocytů; fibrilace síní; lidé středního věku; elektivní chirurgické výkony; senioři; akutní koronární syndrom; mužské pohlaví; Fibrinolytic Agents; Middle Aged; management nemoci; Drug Therapy, Combination; Humans